2002
DOI: 10.1177/021849230201000304
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass in Patients with Severe Left Ventricular Dysfunction

Abstract: We retrospectively reviewed the case records of 82 patients with severe left ventricular dysfunction (ejection fraction < 30%) who underwent coronary artery bypass grafting between March 1993 and February 2000. They were aged 28 to 76 years (mean, 60 years), and 66 of them were male. Significant comorbid factors included hypertension (93%), diabetes mellitus (85%), and hypercholesterolemia (49%). The number of grafts used ranged from 1 to 3. The majority of the patients (91%) belonged to the Canadian Cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…4,7,8,10,15 In our study the hospital mortality was 11%, and only 7% of deaths were cardiac-related, which compares well with most studies. Most of the hospital deaths occurred in the earlier period (early 1990s), and after 2000 only 2 hospital deaths occurred.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4,7,8,10,15 In our study the hospital mortality was 11%, and only 7% of deaths were cardiac-related, which compares well with most studies. Most of the hospital deaths occurred in the earlier period (early 1990s), and after 2000 only 2 hospital deaths occurred.…”
Section: Discussionsupporting
confidence: 89%
“…5,6 Many other groups have reported improvements in survival, ventricular function, and functional status after coronary revascularization in patients with severe LV dysfunction. [7][8][9][10] It is believed that the apparent improvements in LVEF, long-term survival, and quality of life following coronary revascularization are related to postoperative myocyte recruitment. Restoration of perfusion resuscitates dormant, viable myocardium and serves to protect the previously functioning portions of the ventricle from further ischemic insults, arrhythmias, and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the patients examined here, an improvement in the NYHA functional classification occurred in all three groups, especially in those who underwent revascularization procedures (Figure 2). Buszman et al also reported improvements in the NYHA functional classification in patients with cardiomyopathy submitted to revascularization procedures; this trend was comparable in both groups [13]. A trial that investigated patients included in the Duke Cardiovascular Disease Databank considered 1,400 patient cases similar to those presented in our study.…”
Section: Discussionsupporting
confidence: 76%
“…When the results obtained with pharmacological treatment were compared to those achieved with operational treatment, it was apparent that regardless of the level of CAD progression, symptoms of heart failure or LV dysfunction, CABG ensured better results at the 10-year follow-up [14]. Buszman et al proved that PCI offers better results than CABG as far as 1-year survival is concerned; however, fewer subsequent interventions were needed after CABG was performed [13]. Hueb et al [15] did not reveal substantial differences with respect to the number of deaths when comparing three strategies for treatment (MT, CABG, PCI).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that the hospital mortality of patients with left ventricular dysfunction ranges from 3% to 15%. [16][17][18][19] In our study, hospital mortality was 6.4%. This ratio is in accordance with the literature data.…”
Section: Discussionsupporting
confidence: 45%